Social Media Influencers on Facebook and Their Impact on Consumers - Janifar Kamal Nova (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2023)
This study aims to pinpoint the elements contributing to social mediainfluencers' (SMIs) popularity and effectiveness in Bangladesh.Additionally, the study aims to determine how these influencers impactconsumers' purchasing decisions. The study employs a quantitative researchapproach, utilizing an online survey questionnaire. The survey involved 208participants who follow at least one social media influencer on Facebook,selected through a random sampling technique. The study's results highlightthat positive reviews and feedback from other followers/consumers are themost potent factors in creating trust towards SMIs. Additionally, thequality of content and SMI's expertise and knowledge in a specific field/topicmatter most to create an audience base. Besides, most followers believe thatexpertise attracts them to SMIs; hence, SMIs should not promote anythingthey do not know much about, representing their trustworthiness andtransparency to the followers. Also, the recommendation of SMIs and theseconsumer-trust-building characteristics are associated. Brands choose SMIsto convey their message to the targeted audience; the findings also revealthat influencers significantly influence consumers' purchasing decisionsthrough their recommendations, and age is one of the independent variablesthat is associated with the recommendations of SMIs.